Typhoon and Agricultural Production Portfolio -Empirical Evidence for a Developing Economy - Thi Xuyen Tran (ZBW - Leibniz Information Centre for Economics, 2021)
In this paper, we investigate whether and how households adjust their agricultural practices such as cultivation and livestock to adapt to a severe typhoon. We, therefore, make use of a natural experiment coming from the strong typhoon Ketsana in 2009. We apply the difference-in-differences approach using micro-data on the household level and spatial data of this severe typhoon. Our empirical findings suggest that households alter their agricultural activities in response to a strong typhoon. While they decrease the area planted for staple crops, i.e., rice and cassava, they tend to purchase more livestock, i.e., pigs, in the short term and in the medium term. Our paper not only indicates the adjustment to the croplivestock system as a livelihood adaptation strategy to a severe typhoon, but it also suggests the shifting trend from crop planting to livestock raising, which emphasizes the contraction of crop farming in the aftermath of this type of event.
Keywords: O12; O13; Q12; Q15; Q54; 330; Typhoon; Agricultural production; Crops; Livestock; Vietnam